Home advantage in sport: an overview of studies on the advantage of playing at home - Nevill, A. M.; Holder, R. L. (Sports Medicine, 1999)
This review identifies the most likely causes of home advantage. The results of previous studies have identified 4 factors thought to be responsible for the home advantage. These can be categorised under the general headings of crowd, learning, travel and rule factors. From the accumulated evidence, rule factors were found to play only a minor role (in a limited number of sports) in contributing to home advantage. Studies investigating the effect of learning factors found that little benefit was to be gained from being familiar with the local conditions when playing at home. There was evidence to suggest that travel factors were responsible for part of the home advantage, provided the journey involved crossing a number of time zones. However, since high levels of home advantage are observed within countries where travel distances are not great. travel factors were not thought to be a major cause of home advantage. The evidence from studies investigating crowd factors appeared to provide the most dominant causes of home advantage. A number of studies provide strong evidence that home advantage increases with crowd size, until the crowd reaches a certain size or consistency (a more balanced number of home and away supporters), after which a peak in home advantage is observed. Two possible mechanisms were proposed to explain these observations: either (i) the crowd is able to raise the performance of the home competitors relative to the away competitors; or (ii) the crowd is able to influence the officials to subconsciously favour the home team. The literature supports the latter to be the most important and dominant explanation. Clearly, it only takes 2 or 3 crucial decisions to go against the away team or in favour of the home team to give the side playing at home the 'edge'.